Review of the impact of the external magnetic field on the characteristics of magnetic nanofluids - Mahmoud M. Selim; Sherif El-Safty; Abdelouahed Tounsi; Mohamed Shenashen (Alexandria Engineering Journal, 2023)
The emergence of nanofluids as high-efficiency thermal transfer media has piqued the curiosity of heat transfer researchers. Nanomaterial has since been used in a variety of industries, including manufacturing, electronics and electrical systems, automobiles, and applications in biology. On the other hand, magnetic nanoparticle-suspended nanofluids have sparked tremendous attention due to their numerous technical and industrial applications. Several investigations have looked into how the external magnetic field affects the characteristics of magnetic nanofluids. The magnetization of the nanoparticles, which may increase the nanofluid's effective thermal conductivity, is one of the external magnetic field's most important effects. The viscosity of the nanofluid may additionally be impacted by the magnetization of the nanoparticles, resulting in magnetorheological behavior. The effects of an external magnetic field on nanofluids were studied in this research. The research evaluates the thermal conductivity and viscosity research on magnet nanofluids that rely on magnetism.